Reading skills of D/deaf students – native signers - Kotowicz, Justyna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
Reading skills of D/deaf students fall behind their hearing peers. The difference in reading skills between D/deaf and hearing children has not decreased for over past three decades. Low level of reading skills in D/deaf students has been associated with their language delay, which is mainly observed in D/deaf children using spoken language that is not fully accessible to “D/deaf individuals” instead of “ppl with hearing impairment”. D/deaf children immersed in sign language since their birth usually do not encounter language problems and they have a potential to become highly-skilled readers. In the present studies we have investigated reading skills of D/deaf students who are native signers of Polish Sign Language. The results have indicated that D/deaf students showed lower level of reading skills than their hearing peers. The present studies call in question Polish education system dedicated to D/deaf students who are native signers. The obtained results suggest that reading classes are probably not adapted to the needs and abilities of highly competent signers.